Situation critical : critique, theory, and early American studies - Cavitch, Max; Connolly, Brian, 1974- (Duke University Press, 2024)
"The contributors to Situation Critical argue for the continued importance of critique to Early American studies, pushing back against both reductivist neo-empiricism and so-called postcritique. Bringing together essays by a diverse group of historians and literary scholars, editors Max Cavitch and Brian Connolly demonstrate that critique is about acknowledging that we are never simply writing better or worse accounts of the past, but accounts of the present as well. The contributors examine topics ranging from the indeterminacy of knowledge and history to Black speculative writing and nineteenth-century epistemology, the role of the unconscious in settler colonialism, and early American writing about masturbation, repression, religion, and secularism and their respective influence on morality. The contributors also offer vital new interpretations of major lines of thought in the history of critique-especially those relating to Freud and Foucault-that will be valuable both for scholars of Early American studies and for scholars of the humanities and interpretive social sciences more broadly. Contributors. Max Cavitch, Brian Connolly, Matthew Crow, John J. Garcia, Christopher Looby, Michael Meranze, Mark J. Miller, Justine S. Murison, Britt Rusert, Ana Schwartz, Joan Wallach Scott, Jordan Alexander Stein"--